Factors Associated with Physical Frailty in Elderly Women with Low Socioeconomic Status in Urban Communities: A Cross-Sectional Study - Rensa Rensa; Siti Setiati; Purwita W Laksmi; Ikhwan Rinaldi (Acta Medica Indonesiana, 2019)
Background: there are differences in factors associated with frailty syndrome in elderly population. The aim of this research was to determine frailty status (fit, pre-frail and frail) and to identify factors associated with physical frailty in urban community-dwelling elderly women. Methods: a cross-sectional study of community-dwelling women aged 60 years and older was conducted in West and Central Jakarta regions, Indonesia, from July until September 2017. The Cardiovascular Health Study (CHS) score was used to determine frailty status (fit/ pre-frail/ frail). Chi-Square Test and logistic regression analysis were used to determine association between independent variables and physical frailty. Results: there were 325 female subjects with a median age of 67 (60–94) years; 95.7% had income below the Provincial Minimum Income of DKI Jakarta in 2017 (<3.3 million IDR≈238 USD/month), and 92.6% had a level of education ≤9 years. Subjects were classified into this following groups: fit (12.6%), pre-frail (63.4%) and frail (24%). Factors associated with physical frailty were age above 70 years old with OR 5.27, lower Barthel Index for Activities of Daily Living (B-ADL) with OR 2.85, depressive symptoms with OR 6.79, and Euro Quality of Life-5 Dimensions (EQ-5D) index with OR 1.96. Conclusion: elderly women in the urban community with low socioeconomic status were classified as fit (12.6%), pre-frail (63.4%) and frail (24%). Factors associated with physical frailty were age above 70 years old, depressive symptoms, lower functional status and health-related quality of life index.